A manikin study comparing the performance of traditional Macintosh laryngoscope, GlideScope®, Airtraq®, and video-optical intubation stylet in endotracheal intubation used by emergency doctors in simulated difficult airway intubation: A pilot study. Issue 3 (May 2023) - Li, Yu On; Wong, Oi Fung; Ko, Shing; Ma, Hing Man; Lit, Chau Hung Albert; Shih, Yau Ngai
Background: The video-optical intubation stylet (VS) is a slim, rigid but flexible intubating device that aids physicians to intubate patients, particularly with difficult airways. Objectives: The objective of this study was to compare the performance of emergency department doctors in using different intubating devices for intubation in an airway manikin simulating different difficult airway scenarios. Methods: Thirty emergency department doctors were recruited in a pilot study. Their performance of using traditional Macintosh laryngoscope, GlideScope ®, Airtraq ® and C-MAC ® Video Stylet were compared in three situations: normal, restricted cervical motion and limited oral aperture. The time for intubation, first attempt success rate, failure rate, dental injury and the subjective ease of different devices by the participants were compared. Result: The mean intubation time by VS in each scenario was significantly shorter compared with other devices (Normal: 19.77s vs 24.67–28.19s, p = 0.014; Cervical restriction: 20.85 vs 26.17–31.26s, p = 0.008; Limited oral aperture:19.03 vs 29.35, p = 0.001). However, there was no significant difference in failure rate or first attempt success rate. The incidence of dental injury was significantly lower with VS than other laryngoscopes (p = 0.001, p < 0.05 and p < 0.05 in normal, cervical restriction and limited oral aperture scenarios, respectively). Moreover, participants appreciated that VS was the easiest device to intubate in each scenario. (p < 0.05 in all scenarios) Conclusion: The performance of VS was comparable to or even better than the commonly used laryngoscopes in the emergency department in airway management. When adequate training is provided, VS can be a potentially good alternative for tracheal intubation in different situations.